2018
DOI: 10.1021/acs.inorgchem.8b02257
|View full text |Cite
|
Sign up to set email alerts
|

Highly Erbium-Doped Nanoplatform with Enhanced Red Emission for Dual-Modal Optical-Imaging-Guided Photodynamic Therapy

Abstract: Generally, luminescence quenching at high doping concentrations typically limits the concentration of doped ions in the lanthanide material to less than 0.05−20 mol %, and this is still a major hindrance in designing nanoplatforms with improved brightness. In this research, a nanoplatform capable of dual-modal imaging and synergetic antitumor cells therapy was designed. NaYF 4 :x%Er@NaXF 4 (x = 5, 25, 50, and 100; X = Lu and Y) core@shell nanoparticles with Er 3+ ion concentration up to 100 mol % were synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…As one promising anticancer technique, photodynamic therapy (PDT) has gained extensive research interest since it was first found by Dougherty et al because of its high selectivity, low side effects, noninvasive features, and low drug resistance. The principle of PDT is that a photosensitizer (PS), which is predelivered to tumor tissues, can effectively utilize photoenergy to convert oxygen molecules around tissues into reactive oxygen species (ROS), including singlet oxygen ( 1 O 2 ), to treat cancer. , However, the efficiency of PDT is limited because the PS cannot target the tumor, thereby damaging normal cells. , Compared with some noncarbon materials, more and more carbon-based nanomaterials [carbon nanotubes, graphene oxide, and carbon dots (CDs), etc.] have been applied in biomedical field due to the low toxicity, eco-friendly and biocompatibility. …”
Section: Introductionmentioning
confidence: 99%
“…As one promising anticancer technique, photodynamic therapy (PDT) has gained extensive research interest since it was first found by Dougherty et al because of its high selectivity, low side effects, noninvasive features, and low drug resistance. The principle of PDT is that a photosensitizer (PS), which is predelivered to tumor tissues, can effectively utilize photoenergy to convert oxygen molecules around tissues into reactive oxygen species (ROS), including singlet oxygen ( 1 O 2 ), to treat cancer. , However, the efficiency of PDT is limited because the PS cannot target the tumor, thereby damaging normal cells. , Compared with some noncarbon materials, more and more carbon-based nanomaterials [carbon nanotubes, graphene oxide, and carbon dots (CDs), etc.] have been applied in biomedical field due to the low toxicity, eco-friendly and biocompatibility. …”
Section: Introductionmentioning
confidence: 99%
“…Most recently, we have designed a core@shell structure and it proved that the surface quenching and concentration quenching effect could be coupled to emit higher red emission. 52 On the basis of this work and the previous related work, we concluded that four main strategies are utilized to resolve the concentration quenching problem: increasing the excitation laser density, coating an inert shell, choosing a nanocrystal with a larger size, and improving the uniform distribution of codopants. However, how to choose the proper doped element and concentration is challenging.…”
Section: ■ Introductionmentioning
confidence: 62%
“…Generally, a high doping concentration of activator (>2%) and sensitizers (>20%) would induce concentration quenching caused by cross relaxation among the activators themselves or to the surface defect. For a long time, the study of lanthanide-doped nanoparticles has been based on low doping levels. Recently, Liu and Almutairi designed a series of high Er 3+ codopant as the core with the inert shell to enhance the UCL intensity. Most recently, we have designed a core@shell structure and it proved that the surface quenching and concentration quenching effect could be coupled to emit higher red emission . On the basis of this work and the previous related work, we concluded that four main strategies are utilized to resolve the concentration quenching problem: increasing the excitation laser density, coating an inert shell, choosing a nanocrystal with a larger size, and improving the uniform distribution of codopants.…”
Section: Introductionmentioning
confidence: 66%
“…There are two obstacles to fabricate advanced phosphors in these two systems. First, the concentration-quenching effect significantly limits the doping ratio of the activator, which results in reduced photon absorption. , This is also challenging in transition-metal-based phosphors (e.g., Mn 2+ -activated phosphors), whose absorption coefficient is often very low because of parity-forbidden and spin-forbidden nature of the d–d transition . The decreased photon absorption directly leads to a low quantum efficiency.…”
Section: Introductionmentioning
confidence: 99%